Meta-analysis of the development of booklets as learning materials in biology learning - Rara Aulia Putri; Zulyusri Zulyusri (Universitas Negeri Yogyakarta, 2026)
and systematically, supported by relevant illustrations, making it easier for students to understand concepts. Before being used in the learning process, booklets must undergo validation to ensure they meet eligibility standards. This study aims to examine the validity of booklet development in biology learning using a descriptive meta-analysis approach. Research data were obtained from scientific articles identified through Google Scholar, in accordance with the PRISMA 2020 guidelines. The initial search yielded 33 articles; the identification, screening, and selection processes were then carried out based on inclusion criteria, resulting in 10 articles that met the requirements for analysis. The analysis focused on four validity components, namely content, language, presentation, and graphics. The synthesis results showed that the booklet's average validity was 88.97%, placing it in the very valid category. Among the four aspects analyzed, the presentation aspect obtained the highest average of 90.11%, followed by the content aspect at 89.48%, the graphic aspect at 88.85%, and the linguistic aspect at 87.43%. These findings indicate that the booklet is highly suitable for use as teaching materials in biology instruction. In addition to providing an overview of the quality of the booklet's validity, the results of this study can also be used as a reference for educators and teaching material developers in designing booklets that meet the suitability standards, as well as serve as a basis for further research focused on developing higher-quality biology teaching materials.